Common methods for the preparation of clean A- and B-type GaN surfaces assessed by STM, RHEED and XPS - Oliver, R; Norenberg, C; Martin, MG; Crossley, A; Castell, M; Briggs, G (2003)
The preparation of clean GaN surfaces is necessary in order to study the fundamental properties of GaN surfaces, a subject of increasing scientific and industrial relevance. Here, we identify the effect of two common surface cleaning treatments (annealing in ammonia, and sputtering in nitrogen followed by in vacuo annealing) on surface reconstruction, morphology and stoichiometry of both A- and B-type GaN, by employing a combination of in situ RHEED and STM, and ex suit XPS, and illustrate the contrasting behaviours of the two surface polarities.